Role of CD18 in the accumulation of eosinophils and neutrophils and local oedema formation in inflammatory reactions in guinea-pig skin. - Teixeira, M. M. (1994)
1. Intradermal injection of the complement fragment C5a des Arg induces local oedema formation that, in rabbits and man, is dependent on circulating neutrophils. Monoclonal antibodies to the leukocyte adhesion molecule CD11/CD18 block neutrophil accumulation and prevent neutrophil-dependent oedema formation. The role of CD11/CD18 in mediating eosinophil accumulation in vivo is less established. In this study we have used an anti-human CD18 monoclonal antibody, 6.5E, to investigate the neutrophil-dependency of oedema formation induced by C5a des Arg in guinea-pig skin. We also studied the role of CD18 in mediating eosinophil accumulation in the same model. 2. Stimulated adhesion of 111In-labelled guinea-pig neutrophils and eosinophils to serum-coated plastic was inhibited in a dose-dependent manner by 6.5E suggesting that the monoclonal antibody recognizes and blocks the guinea-pig CD18 adhesion molecule. 3. The accumulation of 111In-labelled neutrophils induced by zymosan-activated plasma (ZAP, as a source of C5a des Arg) in skin sites was reduced by up to 89% in animals treated intravenously with F(ab')2 fragments of 6.5E. ZAP-induced accumulation of 111In-labelled eosinophils was also greatly reduced (by up to 78%) by treatment with 6.5E. 4. Despite the inhibition of ZAP-induced neutrophil accumulation by 6.5E, local oedema formation in the same skin sites was unaffected, except at the top dose of ZAP, by treatment with the anti-CD18 monoclonal antibody, suggesting that the oedema response was largely neutrophil-independent. Indeed, ZAP-induced oedema formation was reduced by up to 81% by the H1 receptor antagonist, mepyramine.(ABSTRACT TRUNCATED AT 250 WORDS)